Impact of thyroid hormones on predicting the occurrence of persistent inflammation, immunosuppression, and catabolism syndrome in patients with sepsis - Zhang, Ling; Tan, Ruoming; Pan, Tingting; Qu, Hongping (Frontiers in Endocrinology, 2024)
Background The prevalence of persistent inflammation, immunosuppression, and catabolism syndrome (PICS) has an upward trend in sepsis patients and can be associated with poor outcomes. Thyroid hormones are expected to be correlated with inflammation, immunity, and metabolism. Thus, the purpose of this study was to evaluate the effect of thyroid hormones on the occurrence of PICS and then further explore the optimal level of them in sepsis. Methods This retrospective observational study used the online database Medical Information Mart for Intensive Care (MIMIC)-IV. Univariate and multivariate logistic regression analyses were employed to determine correlations between thyroid hormone levels and PICS. A combination of independent PICS development factors was established with accuracy assessed using the area under the receiver operating characteristic curve (AUC-ROC). Results Patients were divided into PICS (n=205) and non-PICS (n=671) groups. The third quartiles of triiodothyronine (T3) (60-80ng/dl) and thyroxine (T4) (5.5-6.8ug/dl) had the lowest PICS incidence and the adjusted odds ratio (OR) was 0.33 (T3, p=0.009) and 0.39 (T4, p=0.006), respectively, compared with the first quartiles of T3 and T4. For patients with a pre-existing T3 deficiency, severe deficiency (T3 <60ng/dl) and a high Sequential Organ Failure Assessment (SOFA) score were significantly related to PICS incidence. The AUC for these combined parameters in predicting PICS occurrence was 0.748 (all patients) and 0.861 (patients without thyroid disease). Conclusions A mild T3 deficiency (60-80ng/dl) was significantly associated with the lowest risk-adjusted PICS occurrence in patients with sepsis. A severe T3 deficiency (<60ng/dl) and a high SOFA score were independent risk factors for PICS occurrence.